'Summer Rose' Caladium - a University of Florida Cultivar for Containers and Landscapes - Zhanao Deng; Brent K. Harbaugh (EDIS)
ENH1042, a 6-page illustrated fact sheet by Zhanao Deng and Brent K. Harbaugh, introduces tuber producers to this new pink fancy-leafed caladium, a replacement cultivar for 'Rosebud'. Published by the UF Department of Environmental Horticulture. Original publication date October 2006. Revised November 2009, March 2013, and November 2016, and November 2019. Deaccessioned from Ask IFAS site August 26, 2021.